Autorzy:Wojciech Babiański, Lech Chańko, Joanna Czarnowska, Grzegorz Janocha
Wydawnictwo:Nowa Era
Rok wydania:2016
Uporządkuj sumy algebraiczne S i T 4.55 gwiazdek na podstawie 11 opinii

`a)` 

`S=x^3-x+2x^4-2=2x^4+x^3-x-1` 

`T=4-x^3+3x^2+x^4=x^4-x^3+3x^2+4` 

 

`S+T=(2x^4+x^3-x-1)+(x^4-x^3+3x^2+4)=` 

`\ \ \ \ \ \ \ \ \ =ul(2x^4)+ul(ul(x^3))-x-ul(ul(ul(1)))+ul(x^4)-ul(ul(x^3))+3x^2+ul(ul(ul(4)))=`  

`\ \ \ \ \ \ \ \ \ =3x^4+3x^2-x+3` 

 

`S-T=(2x^4+x^3-x-1)-(x^4-x^3+3x^2+4)=` 

`\ \ \ \ \ \ \ \ \ =ul(2x^4)+ul(ul(x^3))-x-ul(ul(ul(1)))-ul(x^4)+ul(ul(x^3))-3x^2-ul(ul(ul(4)))=` 

`\ \ \ \ \ \ \ \ \ =x^4+2x^3-3x^2-x-5` 

 

 

 

`b)` 

`S=-2x^2+4x-x^6+2=-x^6-2x^2+4x+2` 

`T=-5x+3x^2+x^6-3x^5=x^6-3x^5+3x^2-5x` 

 

`S+T=(-x^6-2x^2+4x+2)+(x^6-3x^5+3x^2-5x)=` 

`\ \ \ \ \ \ \ \ \ =ul(-x^6)-ul(ul(2x^2))+ul(ul(ul(4x)))+2+ul(x^6)-3x^5+ul(ul(3x^2))-ul(ul(ul(5x)))=` 

`\ \ \ \ \ \ \ \ \ =-3x^5+x^2-x+2` 

 

`S-T=(-x^6-2x^2+4x+2)-(x^6-3x^5+3x^2-5x)=` 

`\ \ \ \ \ \ \ \ \ =ul(-x^6)-ul(ul(2x^2))+ul(ul(ul(4x)))+2-ul(x^6)+3x^5-ul(ul(3x^2))+ul(ul(ul(5x)))=`  

`\ \ \ \ \ \ \ \ \ =-2x^6+3x^5-5x^2+9x+2`